A state-wide quality improvement system utilising nurse-led clinics for clozapine management. (June 2014) - Clark, Scott R; Wilton, Lisa; Baune, Bernhard T; Procter, Nicholas; Hustig, Harry
Objectives: This paper describes the implementation of a state-wide clozapine management system to improve the quality of care for those with treatment-resistant schizophrenia. This intervention includes standardised forms, computer-based monitoring and alerting and nurse-led clinics for stable consumers. Methods: Methods used during system development included medical record and clinical information system audit, consensus review of available evidence and qualitative review of existing forms, systems and stakeholder opinion. Results: Nurse-led monitoring safely reduced medical outpatient appointments by 119 per week in metropolitan public clinics. In the 15 months following the implementation of all interventions, mortality associated with physical illness not related to malignancy was reduced from an average of 5 deaths per year to one. Conclusions: Differing interpretations of clozapine guidelines have contributed to confusion around monitoring. Standardised documentation has helped to increase understanding and improve protocol adherence. A regular training programme has increased basic knowledge of risks and protocols. Computer-based documentation and alerting systems have improved communication between hospital and community-based teams and prompted early intervention reducing the risk of adverse events. These factors have combined to help improve outcomes in clozapine management. Nurse-led clinics are a safe and efficient alternative for monitoring clozapine treatment.